Effect of rice bran on properties of yogurt: Comparison between addition of bran before fermentation and after fermentation. (February 2023) - Wu, Tongfeng; Deng, Chong; Luo, Shunjing; Liu, Chengmei; Hu, Xiuting
Abstract: Recently, fortifying yogurt with dietary fiber has attracted considerable interest. Since fermentation by lactic acid bacteria might alter the fiber composition and structure, adding fiber into yogurt before and after fermentation might have different effects on properties of yogurt. Therefore, this work investigated effects of adding rice bran before and after fermentation on properties of yogurt to choose a better approach of fortifying yogurt with dietary fiber. Adding rice bran before fermentation significantly decreased syneresis of yogurt at the content of 2.0% and 3.0%, while adding rice bran after fermentation increased syneresis of yogurt. Scanning electron microscopy and confocal laser scanning microscopy analysis indicated that the yogurt gel with rice bran added before fermentation was more compact and porous than the yogurt gel with rice bran added after fermentation. Moreover, the autofluorescence from rice bran added after fermentation was significantly stronger than that in rice bran added before fermentation. Compared with yogurt added with rice bran after fermentation, yogurt added with rice bran before fermentation had higher free p -hydroxybenzoic acid, p -coumaric acid, ferulic acid and sinapic acid contents. These results suggested that fermentation converted bound phenolic acids of rice bran into free ones, which was beneficial to improve the yogurt stability. Thus, the pH, texture and rheological properties of yogurt added with rice bran before fermentation were investigated. It was found that rice bran increased the pH and decreased firmness, consistency, cohesiveness, viscosity and gel strength of yogurt. Graphical abstract: Adding rice bran before fermentation improved the yogurt stability, while adding rice bran after fermentation decreased the yogurt stability. Moreover, the fluorescence in yogurt with rice bran added after fermentation was significantly stronger than that in yogurt with rice bran added before fermentation, which suggested that the bound phenolic acid content in bran was decreased by fermentation. Image 1 Highlights: Rice bran added before fermentation improved the yogurt stability. Rice bran added after fermentation decreased the yogurt stability. Adding rice bran before fermentation made yogurt more compact and porous. Fermentation converted bound phenolic acids in rice bran to their free forms. Adding rice bran before fermentation decreased the apparent viscosity of yogurt.